Quantum technologies with Rydberg atoms - Barik, Shovan Kanti; Thakur, Aishwarya; Jindal, Yashica; S, Silpa B.; Roy, Sanjukta (Frontiers in Quantum Science and Technology, 2024)
Rydberg atoms have highly controllable exotic properties such as strong inter-atomic interaction, high polarizability, and long lifetimes which enabled unprecedented progress in Rydberg atombased quantum Technologies. We present a brief review of recent progress in the development of quantum technologies using Rydberg atoms. We highlight the recent advances in the various regimes of quantum technologies such as quantum Information processing, quantum sensing, quantum simulation of many-body physics and single-photon sources for quantum communications.